Peaceful co-existence in the light of holy Qur’an: A case study of christians living in Kuala Lumpur / Samad Yousefi - Samad , Yousefi (2015)
Peaceful co-existence between religions in this contemporary age is both an individual and social necessity. It is particularly important given the interconnectedness of today’s world in various areas such as politics, economics, society and culture. Isolation is not conducive to progress and development. In this context, the importance of research in the field of peaceful co-existence between Muslims and Christians is highlighted. In this research, Kuala Lumpur is selected as a case study of co-existence between Muslims and Christians due to it constituting a living city that exemplifies such co-existence. In addition, its inhabitants have managed, in spite of the difficult political, economic, cultural and social conditions, to provide the finest images of peaceful coexistence, and by virtue of this deserve to live in this blessed city. The aim of this study is to introduce a contemporary understanding of the concept of peaceful co-existence and religious tolerance among Muslims and Christians through a proper understanding of the provisions of Allah, the Lord of all divine religions through al-Qur’an. The research illustrates how religious co-existence is the means of communication between civilizations, cultural exchange, and the confluence of nations for the good of humanity. Furthermore, the research explores the historical and geographical importance of Kuala Lumpur among the followers of the Abrahamic religions as a living model worthy of emulation. This research adopts the applied descriptive approach to achieve the targeted.